Navigating Carbon Pricing: The Economic and Strategic Implications for Industrial Enterprises - Gangodawilage, Damith (Yayasan Sinergi Kawula Muda, 2024)
Carbon taxation has emerged as a crucial policy tool for reducing industrial carbon emissions and promoting sustainability. This study examines the financial and strategic implications of carbon taxes on industrial firms, particularly in Indonesia, where the policy is gaining traction. Using a qualitative case study approach, data were collected through in-depth interviews with 12 key stakeholders, including corporate tax officers, policymakers, business owners, and representatives from small and medium enterprises (SMEs). The findings reveal that carbon taxes impose additional financial burdens on industries heavily reliant on fossil fuels, compelling firms to adopt adaptive strategies such as energy efficiency measures, investment in green technology, and participation in carbon credit markets. However, SMEs face greater challenges due to financial constraints and limited access to regulatory information. Furthermore, the study emphasizes the importance of regulatory stability, government incentives, and industry-specific support mechanisms in facilitating a smoother transition towards sustainable business practices. The results contribute to the growing discourse on environmental taxation by providing empirical evidence on corporate adaptation strategies and financial planning under carbon pricing schemes. These insights offer valuable implications for policymakers in designing effective tax policies that balance economic growth with environmental sustainability. Future research should examine the long-term impact of carbon taxation on industrial competitiveness and explore the role of digital innovations, such as blockchain-based carbon tracking, in enhancing tax compliance and corporate sustainability initiatives.